Pendidikan Islam pada zaman Abbasyiah (Masa keemasan pendidikan Islam 750-1258 M) - Vera, Andi Ana; Rama, Bahaking; S, Syamsuddin (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This paper discusses the development of Islamic education during the Abbasid Dynasty, known as the golden era of Islam. During this period, Islamic education experienced remarkable progress with the establishment of various educational institutions such as kuttabs, madrasas, libraries, and hospitals. The Abbasid caliphs not only supported religious sciences but also encouraged the advancement of knowledge and technology. The tradition of translating foreign works and conducting scientific studies became a hallmark of this era, producing many prominent Muslim scholars. This study aims to elaborate on the history of the Abbasid Dynasty, the development of educational institutions, and their influence on modern Islamic education. It is hoped that this research can contribute to understanding a comprehensive model of Islamic education that is relevant to the current context.